Novel thiophene derivatives with sulfonamide, isoxazole, benzothiazole, quinoline and anthracene moieties as potential anticancer agents - Ghorab Mostafa M.; Bashandy Mahmoud S.; Alsaid Mansour S. (Acta Pharmaceutica)
A novel series of thiophenes having biologically active sulfonamide 2-11, 3-methylisoxazole 12, 4-methoxybenzo[d] thiazole 13, quinoline 14, 15, benzoylphenylamino 16, and anthracene-9,10-dione 17 moieties were prepared. Structures of the newly synthesized compounds were established by elemental analysis and spectral data. All newly synthesized compounds were evaluated for their in vitro anticancer activity against human breast cancer cell line (MCF7). Most of the screened compounds showed cytotoxic activities compared to doxorubicin as a positive control. Compounds 6, 7, 9 and 13 (IC50 values 10.25, 9.70, 9.55 and 9.39 μmol L-1) revealed higher cytotoxic activities than that of doxorubicin (IC50 = 32.00 μmol L-1). Also, compounds 5, 8 and 10 were found nearly as active as doxorubicin (IC50 28.85, 23.48 and 27.51 μmol L-1).